The Roles of UmuD in Regulating Mutagenesis - Jaylene N. Ollivierre; Jing Fang; Penny J. Beuning (Journal of Nucleic Acids)
All organisms are subject to DNA damage from both endogenous and environmental sources. DNA damage that is not fully repaired can lead to mutations. Mutagenesis is now understood to be an active process, in part facilitated by lower-fidelity DNA polymerases that replicate DNA in an error-prone manner. Y-family DNA polymerases, found throughout all domains of life, are characterized by their lower fidelity on undamaged DNA and their specialized ability to copy damaged DNA. Two E. coli Y-family DNA polymerases are responsible for copying damaged DNA as well as for mutagenesis. These DNA polymerases interact with different forms of UmuD, a dynamic protein that regulates mutagenesis. The UmuD gene products, regulated by the SOS response, exist in two principal forms: UmuD2, which prevents mutagenesis, and UmuD2′, which facilitates UV-induced mutagenesis. This paper focuses on the multiple conformations of the UmuD gene products and how their protein interactions regulate mutagenesis.